2020
DOI: 10.1002/pa.2242
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation and the efficiency of SMEs: The role of government financial incentives in an emerging industry

Abstract: This study examines the moderating role of government financial incentives on the relationship between each dimension of entrepreneurial orientation (i.e., innovativeness, proactiveness and risk‐taking) on the efficiency of SMEs. Data were collected through a structured questionnaire using a sample size of 260 SMEs operating in Pakistan, an emerging economy. The findings indicate that two dimensions of entrepreneurial orientation (i.e., innovativeness and proactiveness) have a significant positive impact on SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…Apart from family participation, many MSMEs rely substantially on government assistance, notably in the financial sector. Government involvement benefits MSMEs significantly in obtaining access to financial resources (Khattak & Shah, 2020). According to a survey conducted by the Indonesian government statistics office, capital concerns are the most prominent challenges faced by MSMEs, and they are the primary reason for their failure to develop.…”
Section: Independencymentioning
confidence: 99%
“…Apart from family participation, many MSMEs rely substantially on government assistance, notably in the financial sector. Government involvement benefits MSMEs significantly in obtaining access to financial resources (Khattak & Shah, 2020). According to a survey conducted by the Indonesian government statistics office, capital concerns are the most prominent challenges faced by MSMEs, and they are the primary reason for their failure to develop.…”
Section: Independencymentioning
confidence: 99%
“…Thereby it is crucial to check the impact of strategic flexibility in developing economies because in developing economies, 90% of organizations have a deficiency of resources and capabilities (Bokhari et al, 2020) which sparked a red light for defending his position as compared to competitors and sustain for long-term (Arnold & Artz, 2015). Hence, many researchers have been studied different factors to sustain the organizational performance for the long-term such as (Khattak & Shah, 2020) on governmental financial support (Imran et al, 2018) on R & D while Awang et al (2009) on environmental factors. However, they all missed the creation of the strategic flexibility of the organization according to the current market situation.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the recent theories and arguments, many researchers believe that EO does not directly contribute to firm performance, but it first creates and crosses market orientation (Amin, Thurasamy, Aldakhil, & Kaswuri, 2016), networking ability (Karami & Tang, 2019), organization culture (Jeong, Ali, Zacca, & Park, 2019), and so forth. In addition to the indirect relationship, studies have also suggested that several moderators such as government financial incentives (Khattak & Shah, 2020a) and observation capacity (Kohtamäki, Heimonen, & Parida, 2019). Moreover, Jiang, Liu, Fey, and Jiang (2018) claimed that resource acquisition plays a significant mediating role between EO and performance.…”
Section: Introductionmentioning
confidence: 99%